Spontaneous rupture of trachea treated conservatively: A case report. (January 2022) - Alamassi, Mohammad; Arabi, Esraa
Abstract: Introduction and importance: Spontaneous rupture of the trachea is a rare, life-threatening condition. Spontaneous rupture associated with corticosteroid use has been rarely reported in the literature. Case presentation: We report a case of a 17-year-old male, a known case of nephrotic syndrome managed by corticosteroid treatment, who presented with diffuse neck and chest swelling after forceful coughing resulting in a spontaneous rupture of the trachea. The diagnosis was established using radiological imaging. The patient was managed conservatively with significant improvement and was discharged shortly. Clinical discussion: Prolonged use of corticosteroids may lead to spontaneous rupture of the trachea due to tracheal wall weakness. Radiological imaging followed by bronchoscopy can be used to confirm the diagnosis. Management can either be conservative or surgical, depending on the case. Conclusion: Conservative treatment by pain relief, intravenous fluids, and antibiotics should be considered an alternative to surgery in selected patients. Highlights: Spontaneous rupture of the trachea is a rare and life-threatening condition. Spontaneous rupture of the trachea can be predisposed by prolonged corticosteroid use. The prompt diagnosis and appropriate management of patients with tracheal rupture are crucial. Diagnostic measures for spontaneous tracheal rupture include radiological imaging with the possible need for bronchoscopy. Tracheal rupture should be suspected in the presence of pneumomediastinum and cervical emphysema without pneumothorax. Tracheal rupture can be managed either conservatively or surgically depending on the patient's whole clinical picture.